Intellectual Property as Collateral: The Future of Indonesian Intellectual Property Legal Policy in Commercial Transactions - Heriyanto, Dodik Setiawan Nur; Gultom, Alif Muhammad (JATISWARA, 2024)
The economic value of Intellectual Property Rights (IPR) is universally recognized and can be utilized as a form of collateral to secure bank loans. The validity of this assertion has been established within the international framework and demonstrated through the established practices of various nations, including the United States and the United Kingdom, which have been analyzed in this research. In response to the remarkable expansion of creative actors, Indonesia implemented Government Regulation No. 24 of 2022 concerning the Creative Economy, which permits the use of intellectual property as collateral for debt to tackle financing obstacles. This research aims to closely examine how intellectual property (IP) is used as a guarantee for loans in Indonesia and other selected jurisdictions. It will investigate the problems and risks tied to this type of lending and discuss possible ways for the government to address these issues. This study discovered that while Indonesian law allows the use of IP as collateral, its actual application is limited due to a lack of understanding among both the general public and business sector regarding the comprehensive policies and procedures. Additionally, this study also proposes potential solutions for the future of IP in commercial transactions as mortgages.